The assessment of fasciola gigantica infection in the rabbit (oryctolagus cuniculus) as a laboratory model parasite development - clinical symptoms and liver pathology (2001)
In this study, the rabbit was assessed as a laboratory host lor the helminthes parasite, Fasciola gigantica. Three groups of rabbits were infected experimentally with 5. 10 and 15 metacercariao of F. gigantica respectively. Clinical signs found included pale mucous membrane, progressive emaciation and rough hair coat. The post mortem findings Included haemorrhage and scattered calcified nodulos on the omentum. Echymosis, fibrosis and necrosis were prominent on the liver in addition to fibrosis and thickening ol the gall bladder and bile ducts. Histopathology of the liver revealed congestion, haemorrhage, cellular infiltration and necrosis. Bile ducts were hyper plastic and dbrotic with severe inflammatory reactions The ova of gigantica were recovered from the faeces of some infected rabbits at 10 weeks post infection Mean number of flukes recovered from the rabbits was 0 in the 5 metacercariae group. 2 in the 10 metacercariao group and 5 in the group given 15 metacercariae.